Selected issues of personal income taxation harmonization - Tomasz Wołowiec (e-Finanse: Financial Internet Quarterly, 2011)
In the process of furthering EU integration little attention was given to the role of income taxes. Multiple income tax systems exist across the Union and their differentiation negatively impacts the European labor market, investments and savings, inhibiting economic growth. Individual nations have little motivation to harmonize as they can engage in tax rate competition and income taxes are interwoven with social security systems that make any attempts at reform extremely complex and politically unpopular. Much of current harmonization is silent”, paralegal, and occurs in response to market forces rather than following a formal plan and through intergovernmental cooperation.
Keywords: H2; H24; J62; K34; 330; EU integration; tax harmonization; personal income taxation; tax system differentiation